Implementation of Android-Based Tailoring Service Ordering Application with Geolocation Integration - Santoso, Muhamad Agung; Sutopo, Joko (Universitas Trilogi, 2023)
Basic needs are an aspect that cannot be separated from human life, and one of the important aspects of these basic needs is clothing which not only functions to protect the body but also plays a role in the world of fashion. To meet these fashion needs, tailoring services have a key role in providing clothes that suit consumer desires. While this need is important, customers often rely on conventional methods, such as word-of-mouth recommendations or seeking out a familiar tailor. Some tailors may have a sign in front of their house, but it is often difficult for potential customers to find and connect with them. Therefore, this research aims to implement a tailor service ordering application that is integrated with geolocation features and can make things easier for tailors and consumers. This application development uses the Java programming language and Android Studio as the framework and Firebase as the database. The result of this research is an application that allows customers to order tailor services via smartphone anywhere and anytime.